Gospel of Sufferings. - Kierkegaard, Søren (2015)
""On the way where a man follows Christ, the height of suffering is the height of glory.""So writes Kierkegaard, long considered the father of existentialism, in his comprehensive explanation of how suffering in all its forms is transformed into joy by faith in God. As an integral part of his 'Edifying Discourses', Gospel of Sufferings bears witness to Kierkegaard's transition from a general religious and philosophical standpoint to a specifically Christian one, forming what is now considered a central plank in the structure of his mature thought. In this classic volume, the great Danish think.